Income Analysis of Eucheuma cottonii Seaweed Farming: A Case Study in Mamuju Regency, Indonesia - Rusli; Junaeda (Pustaka Digital Indonesia, 2022)
This study aims to analyze the income generated from Eucheuma cottonii seaweed farming by identifying the total production costs, gross income, and net income obtained by seaweed farmers. The research was conducted in Mamuju Regency, where the population comprised 156 seaweed farmers. A purposive sampling technique was employed, selecting 15% of the population, resulting in a sample of 23 respondents. The study took place from July to August 2022 and utilized both quantitative and qualitative approaches. Data were collected from primary sources through direct interviews and questionnaires, as well as from secondary sources such as official reports and related literature. The findings indicate that Eucheuma cottonii farmers actively attempt to minimize production costs to maximize profitability. The analysis shows that the average production cost incurred per farming cycle was IDR 5,904,706. In contrast, the average gross income reached IDR 10,496,739, leading to an average net income of IDR 4,595,294. These results suggest that Eucheuma cottonii seaweed farming contributes significantly to the economic well-being of coastal communities. The relatively high net income reflects the potential of seaweed cultivation as a sustainable livelihood option in marine-based economies. Overall, the study highlights the economic viability of Eucheuma cottonii cultivation and supports its development as an income-generating activity for small-scale farmers in coastal regions.